PENGARUH PERUBAHAN HARGA AYAM TERHADAP PERMINTAAN AYAM DI PASAR LOKTUAN BONTANG - Adkhan, Muhammad Jeni (EKONOMIA, 2014)
The purpose and usefulness that is expected of this research is to know and to evaluate or whether or not there is significant influence from its price swings chicken against the number of requests in the Loktuan market of Bontang and elastic or failure of change of prices to influence the demand for chicken.The problem of this research is whether change the price of chicken influential significantly against demand for chicken and do change the price of chicken is chicken the elastic against demand in the Loktuan Bontang market.Market management is the analysis, planing, implementation and controling, programs aimed at the exchange raises the targeted market, with a view to achieving the â€œobjectiveâ€ marketing organization. The first hipothesis of the study is the chicken rice changes significantly effect the demand for chicken in the market Loktuan Bontang, and the second hypothesis is the price elasticity of chicken demand is elastic.The Data have been compiled in a linear regression analysis using simple. The formula used to calculate simple linear regression: Y = a x b. The author uses the program SPSS.The population of this research is the merchant market Loktuan sample, while Bontang is the smallest part of the population that is considered to be representative or can represent the answers of the respondents as a whole. In this study, researchers took four samples.Based on the results of analysis and discussion, pointed out that the price of chicken demand significantly to affect the market Loktuan Bontang. These findings support the hypothesis first. And the price elasticity of demand is elastic cock. This finding received a second hypothesis.